A Web Application for TSP Travel Route System Methodology: An Experimental - Sibaroni, Yuliant; ., Fitriyani; Nhita, Fhira (International Journal of Engineering and Technology, 2019)
The shortest route in tourism application has been developed by some researchers. Generally, the focus of research in comparison some method in obtaining the shortest route between two locations. All these research is useful to find the optimal route between two locations that contains one origin place and one destination place. But when the number of destination places is bigger than one, all these research become un-useful. In tourism, TSP travel route is important for the traveler of the group especially when they want to visit some destination travel locations in a one-day trip.Â The optimal TSP travel route can make the traveler of a group plan their traveling optimally.Â Google as a big company in web service has provided well environment to develop TSP travel route efficiently. In this research, we want to test the feasibility of TSP travel route application that developed by using google service. The TSP travel route that was produced by using google service then compared with TSP solution by manual computation. The experiment result shows that TSP travel route application based on google service can give similar travel route recommendation as manual computation based on shortest distance. This application is feasible but only in small scale. In large scale, development of system including real map and streets, special computation function for distance matrix and TSP solution have to built by our self.Â